1999
DOI: 10.1016/s0896-6273(00)80686-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Generating the Autonomous cAMP-Dependent Protein Kinase Required for Long-Term Facilitation in Aplysia

Abstract: The formation of a persistently active cAMP-dependent protein kinase (PKA) is critical for establishing long-term synaptic facilitation (LTF) in Aplysia. The injection of bovine catalytic (C) subunits into sensory neurons is sufficient to produce protein synthesis-dependent LTF. Early in the LTF induced by serotonin (5-HT), an autonomous PKA is generated through the ubiquitin-proteasome-mediated proteolysis of regulatory (R) subunits. The degradation of R occurs during an early time window and appears to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(151 citation statements)
references
References 64 publications
3
148
0
Order By: Relevance
“…Only the dissociated catalytic subunits are active and capable of activating CREB by phosphorylating it at Ser-133. cAMP also regulates the proteosomal degradation of the regulatory subunits of PKA (13). To determine whether the loss of PKA activity in response to A␤ treatment was due to a failure to degrade the regulatory subunit, we examined the levels of isoform II␣ of the PKA regulatory subunit, the predominant neuronal isoform, as a function of exposure to A␤ .…”
Section: Resultsmentioning
confidence: 99%
“…Only the dissociated catalytic subunits are active and capable of activating CREB by phosphorylating it at Ser-133. cAMP also regulates the proteosomal degradation of the regulatory subunits of PKA (13). To determine whether the loss of PKA activity in response to A␤ treatment was due to a failure to degrade the regulatory subunit, we examined the levels of isoform II␣ of the PKA regulatory subunit, the predominant neuronal isoform, as a function of exposure to A␤ .…”
Section: Resultsmentioning
confidence: 99%
“…When degradation of an inhibitory protein is necessary for memory consolidation, proteasome inhibitors blocked the formation of longterm memory (Chain et al, 1999;Lopez-Salon et al, 2001;Upadhya et al, 2004). Conversely, when UPS functioned as an inhibitory constraint, removal of constraint by proteasome inhibitor enhanced synaptic transmission and facilitated memory formation (Zhao et al, 2003;Yeh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ap-uch was found to be critical for induction of LTF (Hegde et al 1997). Subsequently, Chain et al (1999) showed that at sensory-motor neuron synapses, injection of lactacystin, a specific proteasome inhibitor blocked induction of LTF. Since R subunits inhibit the activity of C subunits of PKA, the results suggested that the UPP operates to remove inhibitory constraints on the formation of long-term memory.…”
Section: The Upp and Long-term Synaptic Plasticitymentioning
confidence: 99%
“…The impetus for closely looking at the regulation of the neuronal proteasome came from conflicting results obtained with proteasome inhibitors on LTF in Aplysia. Originally, it was found that proteasome inhibitors block the induction of LTF (Chain et al 1999). Later studies on LTF, however, showed that bath application of the active form of lactacystin, clasto-lactacystin b-lactone, to sensory-motor neuron synapses resulted in enhanced LTF and an increase in neurite outgrowth in isolated sensory neuron (Zhao et al 2003).…”
Section: Does the Proteasome Have Local Roles In Synaptic Plasticity?mentioning
confidence: 99%
See 1 more Smart Citation